Physicochemical properties of yam starch: effect on textural quality of yam food product (pounded yam) - Otegbayo, B.; Bokanga, M.; Asiedu, Robert (2011)
Yam (Dioscorea spp.) is the second most important root and tuber crop in Africa after cassava. This study was conducted to determine the relationship between physicochemical properties of yam starch (amylose and amylopectin, swelling, solubility and water binding capacity) and the textural quality (stretchability, cohesiveness, adhesiveness, hardness) of pounded yam, a major food product in West Africa. Yam starch was extracted from six tubers each of Dioscorea alata and D. rotundata and their physicochemical properties were determined by standard methods. Pounded yam was prepared from the same set of tubers. Textural quality evaluation was conducted on the pounded yam samples by sensory texture profiling. Data generated were evaluated by canonical correlation analysis. Results showed that D. rotundata with high swelling power, low amylose and water binding capacity gave pounded yam samples, which were cohesive, stretchable, moderately soft and less sticky compared to D. alata with high amylose, water binding capacity and low swelling power that gave pounded yam samples, which were very soft, unstretchable, sticky and incohesive. Canonical analysis showed significant associations (P<0.05) between the physicochemical properties and textural quality of pounded yam samples. These results from D. rotundata were further validated using eighteen other randomly selected yam varieties from this yam species. The reproducibility of physicochemical parameters for the assessment of food textural quality was established. Thus, they can serve as indicators of food textural quality in the selection of yam for food quality by breeders and processors.